Is it possible to tame fear through sport? Occurrence, diagnostics and therapeutic methods of fear of falling - literature overview - Miazga, Małgorzata; Golemo, Jagna; Serkis, Barbara; Bentkowska, Zuzanna; Bogoń, Aleksandra; Ostojska, Magdalena; Kałuża, Izabela; Szpyra, Justyna; Celichowska, Magdalena; Górska, Magdalena (Quality in Sport, 2024)
Introduction: Fear of falling is described as a natural response to unstable balance resulting problems with postural control. It usually occurs in older people suffering from chronic diseases and lowers their quality of life. Importantly, general physical activity is limited by the fear of falling, which makes everyday functioning difficult. Aim of the study: The aim of this paper is to present and submit the latest discoveries regarding the topic of fear of falling and physical activity. Material and Methods: This article was created based on the PubMed and Scholar database.The literature was reviewed using the keywords: „fear of falling”; „physical activity”. Results: Research shows that there are many chronic diseases, for example diabetic neuropathy, Parkinson's disease or hip fractures, that may predispose patients to fear of falling. The Falls Efficacy Scale - International (FES-I) is one of the several tools to assess fear of falling, which facilitates the selection of appropriate care and interventions. Well-selected exercises such as the Otago programme, can be implemented to reduce this problem. Generally physical activity combined with the proper encouragement to exercise at home is highly effective in reducing the fear of falling. Conclusion: Considering that more and more people may be exposed to the experience fear of falling it seems significant how to combat this problem. There are appropriate methods to assess and interventions which can be implemented to reduce fear of falling by clinicians, but further studies are still needed.